The Ideology Of Law: Embodying The Religiosity Of Pancasila In Indonesia Legal Concepts - Sinung Mufti Hangabei; Khudzaifah Dimyati; Absori Absori; Akhmad Akhmad (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2021)
The Pancasila ideology is positioned as the source of all sources of law in Indonesia. This meaning cannot be separated from the ideal value of the Indonesian Nation, which is God Almighty. This paper discusses the understanding of religious dimension of Pancasila as a legal norm, so that the applicable law can achieve its objectives. The normative and philosophical approach methods show that Pancasila has the roots of religiosity in its formation. The results of the study show that the strengthening of substantial ideological thinking based on social values that live in society and cannot be separated from the religious values of Pancasila becomes a place where law carries out its functions and roles in the life of the nation and state. In conclusion, the basic norms of the state, Pancasila, which have a religious dimension, are used as a benchmark in assessing the validity of the established regulations. The purpose of law is inseparable from the ultimate goal in the life of the nation and state, namely the values and philosophy of community life itself. The legal construction that puts aside Indonesian values in the context of ideology and the ideology of Pancasila law will result in the law losing its